Higher Education Students’ Perceptions of Environmental Issues and Media Coverage - Keinonen Tuula; Palmberg Irmeli; Kukkonen Jari; Yli-Panula Eija; Persson Christel; Vilkonis Rytis (Discourse and Communication for Sustainable Education, 2016)
This study aims to find higher education students’ perceptions about environmental issues and how the perceptions are related to perceptions of media coverage. This study investigates higher education students’ perceptions of the seriousness of environmental issues and their relation to perceptions of media coverage. Higher education students perceived a global problem, lack of clean water, as most serious environmental problem. Media has had an effect on students’ perceptions on environmental issues: when students perceived the problem as serious they also perceived the information in media concerning it appropriate. Students perceived that the media underestimate and obscure some environmental problems such as biological diversity and global warming. It was concluded that higher education educators need more knowledge of students’, future decision makers’ concerns and perceptions about environmental issues to develop more effective teaching practices in higher education. Through education environmental issues literacy, which is a precursor for engaged protection of the environment, can be fostered. This study offers some insights into higher education students’ perceptions of the media’s role in environmental issues.